Polityczne zaangażowanie mniejszości polskiej na Litwie po wyborach parlamentarnych 2012 roku - Sidorkiewicz, Krzysztof (Polityka i Społeczeństwo, 2021)
The article presents an analysis of the activities undertaken by Poles in Lithuania following the parliamentary election of 2012. The Polish minority took an active part in the Lithuanian politics. Związek Polaków na Litwie [The Union of Poles in Lithuania] followed by Akcja Wyborcza Polaków na Litwie [Electoral Action of Poles in Lithuania] presented their programs for the coming elections. Their involvement in the Lithuanian politics at the national level enabled them to articulate issues important for the Polish community in Lithuania. AWPL participated in the governing coalition. The political circumstances made their proposed solutions not easy to implement. Some problems were temporarily resolved, while most of the important issues remained under discussion. The analysis is based on various documents: agreements, treaties, declarations, statements. Also, it uses press material available in the Internet editions.